Metriocnemus erythranthei sp. nov. and Limnophyes viribus sp. nov. (Diptera: Chironomidae: Orthocladiinae): leafminers of monkeyflowers, speedwells, and other herbaceous plants, with new observations on the ecology and habitats of other leaf-mining Chironomidae - Eiseman, Charles S.; Namayandeh, Armin; Linden, John Van Der; Palmer, Michael W. (Zootaxa, 2023)
In this study, we describe Metriocnemus erythranthei sp. nov. and Limnophyes viribus sp. nov., leafminers of herbaceous wetland plants. The M. erythranthei larva is a true miner entering fresh leaves and excavating the tunnels, and the L. viribus larva inhabits vacated mines of M. erythranthei. M. erythranthei is widespread in North America, with collections from the Pacific coast to Pennsylvania, and L. viribus has been collected from Iowa and Oregon. We also describe the larva of a possible new species associated with these plants, which we refer to as Metriocnemus sp. “Oregon”. A key to the known larval stages of North American Metriocnemus is also provided. Along with providing a detailed account of the mining ecology of these new species, we discuss additional observations of mostly Orthocladiinae midges associated with aquatic and terrestrial plants. These include documenting the rearing of Metriocnemus eurynotus (Holmgren, 1883) from larvae feeding on Impatiens (Balsaminaceae) cotyledons, initially as leafminers and later externally. Larvae of M. eurynotus also were found feeding within mines of M. erythranthei on Veronica (Plantaginaceae) and were collected along with M. erythranthei larvae on leaves of Petasites (Asteraceae).